Brief Report: No Association Between Parental Age and Extreme Social-Communicative Autistic Traits in the General Population. - Robinson, Elise; Munir, Kerim; McCormick, Marie; Koenen, Karestan; Santangelo, Susan (Journal of Autism & Developmental Disorders, 2011)
This is the first investigation of the relationship between parental age and extreme social-communicative autistic traits in the general population. The parents of 5,246 children in the Avon Longitudinal Study of Parents and Children (ALSPAC) completed the Social and Communication Disorders Checklist (SCDC). The association between parental age and SCDC scores was assessed in the full sample and among high scoring individuals (e.g. top 5%, 1%). There was no association between parental age and social-communicative autistic traits in the general population. Neither maternal nor paternal age was associated with extreme scores. These findings suggest that advanced parental age does not confer increased risk for extreme social and communication impairment assessed quantitatively.